Welfare Pricing and Transport Costs - Tyndall, D. G. (Management Science, 1959)
This paper attacks the problem of setting prices and outputs in a set of plants producing a given commodity but having differing cost-output functions, where producing and consuming locations are separated geographically so that transport cost in some (or all) cases are significantly greater than zero. We seek an optimal allocation of resources within the framework of orthodox welfare assumptions. Where Marginal Cost functions are non-decreasing, optimality is achieved at the classical competitive equilibrium point. Our problem is to determine this point. Given cost and demand functions of simple types, a solution can be obtained by programming methods, e.g., the Simplex method. However, where the number of significant producing and consuming locations is small, a simple iterative procedure can be applied even though the cost and demand functions be quite complex.